Idealism, Deadlock and Decimation: The Italian Experience of World War I in Ernest Hemingway’s A Farewell to Arms and Emilio Lussu’s Sardinian Brigade - Quinn, Patrick J.; Trout, Steven (The Kent State University, 2013)
In Hemingway’s fiction, the Italian theater of World War I is a theater of the absurd, alongside which even the notorious Western Front has a measure of dignity and purpose. France may have “ghastly show[s]” like the Somme or Verdun, but it is there that the real war is being fought and where its final outcome will be decided (Hemingway, A Farewell to Arms 18).
FSM Vakıf Üniversitesi, Medeniyetler İttifakı Enstitüsü